Knowledge and attitude of general dentists regarding common emergencies in dental offices: A cross-sectional study in Shiraz, Iran - Azita Azad; Zahra Talattof; Zahra Deilami; Maryam Zahed; Amir Karimi (Wolters Kluwer Medknow Publications, 2018)
Background: Medical emergencies are likely to occur in dental offices due to the use of anesthetics, anxiety, and systemic complications of the patient. Since such emergencies are life threatening in many cases, preparedness of the dentist is highly required. Aims: This study was carried out to evaluate the dentists' knowledge and attitude regarding diagnosis and treatment of medical emergencies in dental offices in Shiraz, Iran. Methods: This cross-sectional study was performed on 150 general dentists in Shiraz with at least 5 years since graduation in 2015. They were asked to complete a validated questionnaire including the dentists' demographic information and inquiries about their performance and knowledge in emergency situations. Statistical Analysis Used: Independent t-test, one-way ANOVA, and Pearson's correlation coefficient were used in this study. Results: According to the inclusion criteria, 105 dentists participated in the study. The mean knowledge and attitude of the dentists was estimated 4.98 (±1.50) out of 10. No significant correlation was detected between age, sex, number of patients per day, and working hours with the knowledge of managing an emergency situation (P > 0.05). Out of the number of studied dentists, 49% had attended training workshops and 90% called for re-attending a workshop. The knowledge score of those who had participated in workshops was significantly higher than those who had not (P = 0.016). Conclusion: The results of this study revealed that the dentists' knowledge about emergency situations was average while the knowledge was higher in those who had attended emergency workshops. Thus, retraining courses and workshops must be considered more often for graduated dentists.